The effectiveness of gas recovery systems for managing odour from conventional effluent treatment ponds in Palm oil mills in Malaysia - Chung, Andrew Yap Kian; Qamaruz Zaman, Nastaein; Yaacof, Narushikin; Yusoff, Syafinah; Abd Manaf, Fatah Yah; Mohamed Halim, Rohaya; Abd Majid, Rusnani (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Gas recovery systems at palm oil mills enable the curtailment of uncontrolled greenhouse gas emissions from open anaerobic pond, but can also reduce odour, an aspect which has not yet been substantiated. The objective of this study is to evaluate the odour emission from palm oil mill effluent and the effectiveness of covers and tank digester in reducing odour emission from the open lagoons.
Keywords: gas recovery systems; palm oil mill effluent; palm oil mills; effluent treatment; anaerobic ponds; reduce odour; reduced gas emission; systemy odzyskiwania gazu; ścieki palmowe; olejarnie palmowe; oczyszczanie ścieków; stawy beztlenowe; redukcja zapachów; redukcja emisji gazów cieplarnianych